Sistem Otomasi Kincir Air Untuk Respirasi Udang Tambak Menggunakan Sensor Dissolved Oxygen (DO) - Ari Fiyanti; Warsito Warsito; Sri Wahyu Suciyati (Jurnal Teori dan Aplikasi Fisika, 2017)
Automation system waterwheel for farmed shrimp respiration have realized using dissolved oxygen sensors (DO). The DO sensor used to detect the levels of dissolved oxygen in the water. Digital data output sensor DO is connected to the computer via the arduino uno, furthermore the output data are recorded and displayed on the LCD monitor and a television series. Automation system using relay with a range of dissolved oxygen levels <4,00 mg/L for the condition of the windmills ON and >5,50 mg/L for the condition of the windmills OFF.